(untitled) (Journal of Educational Sciences, 2023)
Critical thinking is one of the most essential skills in the education system of modern society. In the field of education, many methods and techniques are used to develop this skill. In this regard, the problem-based learning method can be considered as the most effective of the various methods. It was investigated the efficiency of Problem-Based Learning (PBL) model as a useful strategy for improving English language learners’ critical thinking skills. The participants of this study were 34 Master Students of Academic Writing program of Khoja Akhmet Yassawi International Kazakh-Turkish University. English language learners were separated into experimental and control groups. The author used pre and post tests as a data collection instrument. In order to analyze the test results a quantitative method and descriptive statistical analysis were applied. The test scores were measured according to the six indicators of Bloom’s Taxonomy thinking levels. The study lasted five weeks and the experimental group was taught online via Google classroom platform. In this research, a mind mapping strategy was used as a brainstorming tool to define and solve problems. It can be noted that the experimental group’s posttest scores and learning outcomes were significantly improved. The experimental group achieved high scores from understanding and evaluation indicators, scoring 79% and 76% higher than the average scores respectively. This means that they can understand and evaluate any information they read or hear. While the other indicators, namely memorization (65%), application (68%) creation (61%) and analysis (51%), were also higher than the previous test scores. The latest results of the study identified the problem-oriented learning (PBL) model as the most effective method for developing critical thinking and recommend its independent application in any educational institution. It was also found that the integrated application of the problem-based learning (PBL) model with the mind mapping strategy can improve English language learners’ critical thinking skills. Key words: critical thinking, Bloom’s Taxonomy, problem-based learning (PBL), mind map, Mind- Meister.